THE DEVELOPMENT OF LEADERSHIP CHARACTERISTICS OF STUDENT COUNCIL MEMBERS BASED ON DUTIYA PAPANIKA SUTTA OF SCHOOLS IN NETWORK CENTER 4 KHAO NANG NON UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Chamnanaksorn, Chopaka; Somkhaoyai, Teeraphong; Klubsr, Suwes (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to 1) study the development state of leadership characteristics of student council members of schools in network center 4 Khao Nang Non, 2) study the guidelines for developing the leadership attributes of student council members based on the principles of the Dutiya Ppanika Sutta, 3) propose guidelines for development of leadership characteristics of student council members based on Dutiya Ppanika Sutta of schools in network center 4 Khao Nang Non Under Nakhon Si Thammarat primary educational service area office 2. This was qualitative research. The data were collected by in-depth interviews with 15 people, 5 experts were interviewed to draft the guidelines, 7 qualified persons were interviewed in focus groups, and data were analyzed using content analysis. The research results were found as follows: 1) The leadership characteristics of the student council members of schools in the Khao Nang Non Network Center 4 comprising with 4 aspects: (1) human relations, (2) responsibility, (3) decision-making and (4) teamwork building. It was found that the student council members lacked cooperation in their work, avoided assisting in activities and required improvement in discipline through regular meeting participation and time management in operations. Continuous monitoring and evaluation of their work were conducted, identifying strengths, weaknesses and problems encountered. Opportunities were provided for expressing opinions and making important decisions. The school organized leadership skill training, focusing on group activities, regular operational meetings, assigning duties based on individual and abilities and closely monitoring advising and mentoring student council members by the responsible teachers. 2) The guidelines for developing the leadership characteristics of student council members in schools within Network Center 4 Khao Nang Non, consisting with four aspects: interpersonal relationships, responsibility, decision-making and team building. These developments were grounded in the principles of the Dutiya Ppanika Sutta which emphasized three key attributes: Cakkhum (visionary thinking and goal-setting), Vidhuro (expertise in specific fields), and Nissayasampanno (interpersonal skills). 3) The results of presenting the guidelines for developing the leadership attributes of student council members in schools under Nakhon Si Thammarat primary educational service area office 2 by 7 qualified persons agreed that it was feasibility, appropriateness, and usefulness.